Transformasi Kelompok Wanita Tani Menjadi Kelompok Sadar Wisata di Kecamatan Punggur Lampung Tengah - Maulana Mukhlis; Yulianto Yulianto (Jurnal Pengabdian Pada Masyarakat, 2020)
THE TRANSFORMATION OF FEMALE FARMER GROUP INTO TOURISM-AWARE GROUP IN PUNGGUR SUB-DISTRICT OF MIDDLE LAMPUNG DISTRICT. Middle Lampung district has potential various tourism object attractions to develop in order to improve public welfare. However, they are not yet utilized optimally because of weak institutional supports in village level. Various local institutions (such as female farmer group) in Badran Sari village (Middle Lampung) so far had showed performances in developing distinctive local fishery/agriculture products, but they were all still packaged in household economy objectives, so that not yet able to attract public attention for tourism objectives. The objective of this service was to form a Tourism-aware Group growing from public awareness that would be supported and developed with proper assistance and education by coordinating with tourism sector stakeholders. Methods to obtain the objective were socialization, assistance, and education to existing female farmer group so that it would transform into “Semenanjung Badran” Tourism-aware Group that was able to operate tourism functions to develop a real Tourism Village and able to improve tourism visits. Post-service evaluation result showed that this service had obtained its objective in the context of understanding and attitude changes of public and commitment from Tourism-aware Group administrators. Quantitatively, pre-test and post-test comparison suggested participants’ understanding, knowledge, and will improvements by 96.06%. Qualitatively, the service result succeeded to convince Tourism-aware Group administrators that tourism sector was an activity touching and involving public directly and potentially affecting public welfare improvement directly in Badran Sari village.